Advantages and Risks of Implementing Electronic Voting: Experience for Ukraine - Duliba, Yevheniia; Teremetskyi , Vladyslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article highlights the advantages and disadvantages of implementing electronic voting worldwide, emphasizing the complex interaction between technological progress and democratic governance. It is noted that while electronic voting is becoming more widespread globally, no country has yet fully transitioned to using electronic voting at all levels of electoral processes, preferring a combination of electronic and traditional (paper) voting and enabling voters to cast their votes online. The benefits of implementing electronic voting, such as convenience, accessibility, accuracy, efficiency, and reducion of labor involvement, are highlighted and analyzed. Considerable attention is given to analyzing the risks associated with electronic voting, including the need for clear regulation in electoral legislation without which electronic voting could be subject to doubts about its legality and correctness, leading to disputes and a lack of public trust in the electoral process overall; ensuring security against cyber threats, technological failures, hacking attacks, malicious software, risks of election fraud, the danger of centralization, and the vulnerability of centralized data, violation of voting secrecy; significant financial expenses for developing, implementing reliable and secure electronic systems, and supporting their operation; breaches in the transparency of the electoral process and emerging mistrust in the final election results. It is concluded that only a balanced approach aimed at addressing issues of security, accessibility, accuracy, verifiability, anonymity, transparency, economic efficiency, and trust can overcome all the challenges of implementing electronic voting in Ukraine and its operation.